Notes to Philosophy 167: Class 13 -- Newton's De Motu Corporum in Gyrum (i.e. Version 1) -- Part 16. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Advances Made by Version 1 of De Motu -- A "Galilean-Huygensian" Theory of Orbital Motion -- Departures from Galilean-Huygensian Science -- Loose Ends in Version 1 of De Motu -- Version 1 of De Motu Versus the Principia.; Generally corresponds to the video segment: Class 13, Part 16.